Three essays on torts - Stapleton, Jane (Clarendon law lectures., 2021)
This book of essays champions tort scholarship that puts judges at centre stage: what they do, how they understand their role, the heterogeneous reasons they give for their decisions, and their constitutional responsibility to identify and articulate the 'living' and 'evolving' common law. This is 'reflexive tort scholarship'. Reflexive tort scholars seek dialogue with Bench and Bar. Their approach is very different from the currently fashionable academic search for 'grand theories' that descriptively assert that tort law is fundamentally 'all about one thing', a unifying idea that alone explaind and justifies the whole of tort law. This book illustrates the advantages and pay-offs of the refexive style of schoolarship by showing how it illinates key features of tort law.